Scientific production on ameloblastomas in GoPubMed and SciELO - Corrales-Reyes, Ibraín Enrique (2018)
Objective: To describe the worldwide scientific production on ameloblastomas indexed in GoPubMed and SciELO databases. Methods: An observational, descriptive cross-sectional study was carried out, considering as a unit of analysis the articles published in journals indexed in GoPubMed and SciELO. The co-authorship and co-occurrence of descriptors networks were created with the VOSviewer software and the full counting method. Results: It was recovered 4 159 articles from GoPubMed with an annual average of 56.97 ± 39.62. There was a predominance of documents published in the period 2010-2014 (n=758; 18.23%) from the United States (n=129; 3.1%) as well as articles published in the journal Oral Surgery Oral Medicine and Oral Pathology (n=40; 0.96%). The researchers Hiroyuki Kumamoto and Chong Huat Siar were the authors with the largest number of articles and networks of co-authorship and international cooperation (36 and 31 respectively). «Ameloblastoma» and «mandibular neoplasms» were the descriptors with the highest number of occurrences. In SciELO, 84 articles were recovered with an annual publication average of 4.94 ± 2.88. There was a predominance of articles of brazilian authorship (n=31; 36.9%), original research (n=41; 48.81%) and documents in Spanish (n=41; 48.81%). Conclusions: There was a tendency to increase research in recent years, with original studies prevailing as well as the creation of international networks of scientific collaboration.